2019
DOI: 10.1155/2019/5937635
|View full text |Cite
|
Sign up to set email alerts
|

BTBD7 Downregulates E-Cadherin and Promotes Epithelial-Mesenchymal Transition in Lung Cancer

Abstract: Metastasis is the leading cause of lung cancer-associated death. Downregulated expression of E-cadherin followed by epithelial-mesenchymal transition (EMT) is critical for metastasis initiation in lung cancer. BTBD7 plays essential roles in lung cancer metastasis, but the mechanisms remain unknown. This study aimed to investigate the relationship between BTBD7 and E-cadherin in lung cancer and explore the role of BTBD7 in EMT. Fresh lung cancer and paracancer tissue specimens were collected from 30 patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…Thus, modulation of EMT can also be of importance in treatment of non-cancerous diseases [125][126][127]. It has been shown that E-cadherin downregulation may be associated with the development of a number of cancers such as breast cancer [128], lung cancer [129], skin cancer [130], and GC [131]. This can be related to the EMT mechanism.…”
Section: Emt Process In Healthy and Cancerous Tissuesmentioning
confidence: 99%
“…Thus, modulation of EMT can also be of importance in treatment of non-cancerous diseases [125][126][127]. It has been shown that E-cadherin downregulation may be associated with the development of a number of cancers such as breast cancer [128], lung cancer [129], skin cancer [130], and GC [131]. This can be related to the EMT mechanism.…”
Section: Emt Process In Healthy and Cancerous Tissuesmentioning
confidence: 99%
“…as the main proteins associated with cell migration. 27 MMP-9 and MMP-1 are proteolytic enzymes that facilitate cell invasion by degrading extracellular matrix, which leads to metastasis. 28 Previous reports indicated that lung CSCs were endowed with EMT characteristics and increased risk for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is considered the most common type of tumor and is a predominant cause of cancer-associated mortality in China ( 1 3 ). Currently, more than 1.5 million cases of mortality are reported from lung carcinomas annually, and the 5-year survival rate is only 17% ( 1 , 4 ). Early stage symptoms of lung cancer are atypical and the majority of the different types of lung cancer are not detected until advanced stage.…”
Section: Introductionmentioning
confidence: 99%